The Subversion of שָׁלַח–Divorce in the Hebrew Bible - 吴孟翰 (中国基督教研究（ISSN：3068-479X）, 2024)
This essay examines how  שָׂנֵא(“to hate”),  עָזַב(“to abandon”), גָּרַשׁ  (“to cast out”), and שָׁלַח (“to send away”) are employed in the Hebrew Bible to denote and connote “divorce.” While the patriarchal values and practices are hard to miss, this essay finds the usages of שָׁלַח outside of Pentateuch, in particular in Isaiah 50, Jeremiah 3 and Malachi 2, subversive with respect to the typically negative representation of women. The metaphoric feature and signification of שָׁלַח should not be overlooked and reduced. As such this essay urges caution in citing the “divorce” imagery in the Hebrew Bible as the support and rationale for one’s agenda.